1999
DOI: 10.1111/j.1751-1097.1999.tb08249.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nuclear Factor‐KB in Colon Cancer Cell Apoptosis Mediated by Aminopyropheophorbide Photosensitization

Abstract: Aminopyropheophorbide (APP) is a second generation of photosensitizer for photodynamic therapy (PDT). We demonstrated that APP strongly absorbed red light and, after being taken up by colon cancer cells (HCT-116 cells), was localized in cytoplasmic and internal membranes but not in mitochondria. The APP-mediated photosensitization was cytotoxic for HCT-116 cells through an induction of apoptosis. Indeed, DNA fragmentation (DNA laddering and terminal deoxyuridine nick-end labeling) and chromatin condensation (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
(22 reference statements)
2
20
0
Order By: Relevance
“…It is thus likely that the active cellular site for triggering apoptosis mediated by PPME photosensitization is the ER/Golgi system. The absence of co-localization with the mitochondrial probe rhodamine-123 indicates the likelihood that the ER/Golgi is the site from which the apoptotic signal originates (Matroule et al, 1999b). Others have found that photosensitizers localize to a variety of cellular sites including the outer membrane, lysosomes, mitochondria and the nucleus resulting in damage to these structures upon light exposure (Morgan et al, 2000;Oleinick and Evans, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It is thus likely that the active cellular site for triggering apoptosis mediated by PPME photosensitization is the ER/Golgi system. The absence of co-localization with the mitochondrial probe rhodamine-123 indicates the likelihood that the ER/Golgi is the site from which the apoptotic signal originates (Matroule et al, 1999b). Others have found that photosensitizers localize to a variety of cellular sites including the outer membrane, lysosomes, mitochondria and the nucleus resulting in damage to these structures upon light exposure (Morgan et al, 2000;Oleinick and Evans, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this case the activation of NF-nB was proposed to occur by a mechanism independent of the activation of InB kinases and require the activity of a tyrosine kinase [227]. Expression of a dominant negative mutant of InBa increased apoptotic death of HCT-116 cells sensitized with APP [228], suggesting that NF-nB regulates the expression of gene(s) encoding proteins with an anti-apoptotic activity. However, it was not determined whether cells prevented from undergoing apoptosis in the presence of the dominant negative mutant of InBa died by a non-apoptotic mechanism.…”
Section: Transcription Nuclear Factor Kappa B (Nf-jb)mentioning
confidence: 99%
“…Furthermore, HeLa cells (human cervix carcinoma cells) and T24 cells (human transitional cell carcinoma of the urinary bladder) photosensitized with hypericin also showed a reduction in the cytosolic levels of InBa, which correlated in time with binding of nuclear proteins to the NF-nB site of the cox-2 promoter [145]. The activation of NF-nB and its role in cell death upon photosensitization was investigated using the sensitizer PPME [160,227] and its derivative aminopyropheophorbide (APP) [228], which results from the addition of a positively charged group that increases cellular uptake. PPME-mediated photosensitization of HCT-116 human colon carcinoma cells activated NF-nB by triggering the signaling pathway mediated by the IL-1 receptor.…”
Section: Transcription Nuclear Factor Kappa B (Nf-jb)mentioning
confidence: 99%
“…Several studies have indicated that NF-κB activation plays a negative role in PDT. Matroule et al found that the HCT-116 cell line, which expresses a dominant-negative mutant of inhibitor-Iκα, was highly sensitive to apoptosis and indicated that NF-κB activation was involved in an anti-apoptotic response to aminopyropheophorbide (APP)-mediated photosensitization [11]. Furthermore, it has been demonstrated that inhibition of NF-κB improves glioblastoma cell death in response to 5-Aminolevulinic acid (5-ALA)-mediated PDT [12].…”
Section: Introductionmentioning
confidence: 99%